Ion-mediated increases in xylem hydraulic conductivity: seasonal differences between coexisting ring- and diffuse-porous temperate tree species - Jupa, Radek; Doubková, Pavlína; Gloser, Vít (Tree physiology, 2019)
Ion-mediated changes in hydraulic conductivity (ΔKh) represent a mechanism allowing plants to regulate the rate of xylem transport. However, the significance of ΔKh for ring-porous (RPS) and diffuse-porous tree species (DPS) remains unknown. Here, we examined ΔKh in young branches of three coexisting, temperate RPS (Fraxinus excelsior, Quercus robur, Robinia pseudoacacia) and three DPS (Acer pseudoplatanus, Carpinus betulus, Fagus sylvatica) across the whole year, and assessed the relationships of ΔKh to branch anatomy. Ring-porous species exhibited twice as high ΔKh (10.3% vs 5.3%) within the growing season (i.e., during wood production) compared with DPS, and the production of the annual ring was identified as a crucial process affecting maximum ΔKh within the season. In addition, xylem in branches of RPS generally contained more axial parenchyma (AP; 18% vs 7%) and was characterized by a greater relative contact fraction between vessels and parenchyma (FVP; 59% vs 18%) than xylem in DPS. Simultaneously, ΔKh measured within the growing season was positively correlated with AP, FVP and bark proportions, suggesting that parenchyma in branches may be important for high ΔKh. Significant increase in ΔKh observed during the growing season may help RPS to restore conductive capacity after winter, better compensate transport loss by drought-induced embolism and thereby improve water delivery to leaves.
Keywords: poréznost; voda; stromy; Trees; Porosity; Xylem; roční období; Seasons; xylém; Water